Characterization of the chloroplast genome of Chlorolobion braunii ITBB-AG6 isolated from a treatment pond of sanitary sewage - Yaojia Mu; Shuai Ma; Deguan Tan; Xuepiao Sun; Jiaming Zhang (Mitochondrial DNA. Part B. Resources, 2023)
Sphaeropleales is an order of fast-growing microalgae with high oil content and high efficiency in sewage treatment, in which photosynthesis plays a critical role. We isolated a strain of Sphaeropleales, Chlorolobion braunii ITBB-AG6 from an azolla community in a sewage pond, and sequenced its chloroplast genome. The complete genome has a length of 154 kb with a GC content of 31.7%. A total of 89 genes were annotated, including 56 protein-coding genes, 30 tRNA genes, and three rRNA genes. Out of the protein coding genes, 64.3% are involved in photosynthesis, 28.6% are involved in protein synthesis, and 7.1% are involved in ATP synthesis. Transfer RNA genes for 20 amino acids were identified, in which tRNA genes for methionine, leucine, and arginine are tripled, whereas tRNA genes for glutamic acid, glycine, serine, and threonine are doubled. Terminal inverted repeats of 27.9 kb containing 10 genes related to photosynthesis and chloroplast division are present in the genome, suggesting that photosynthesis was strengthened in the evolutionary history. Phylogenetic analysis indicates that C. braunii ITBB-AG6 falls in the family Selenastraceae and is most closely related to Monoraphidium neglectum.